(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Today the world is rapidly developing and the process of globalization is deepening. In such conditions, of course, being able to speak several languages opens the door to a wide range of opportunities to live in harmony with the world. This article is about learning foreign languages in an easy and understandable way with the help of games.